Life Obstacles to Wheat Crop in some Administrative Units in Basra Governorate - Kamel Abdulhassan Al-Saad , Lect. Saba (Basra studies journal, 2023)
group of life factors share in crystallizing many obstacles that stand in the way of the wheat crop, as the crop is exposed to many diseases, agricultural pests and harmful jungles. Some climatic conditions in the study area helped create a suitable environment for such diseases and pests, including high temperatures, dry winds, the different balance of basic nutrients in the soil and other conditions. The results of the study showed the spread of many pests that cause diseases to the wheat crop, and perhaps the most important harmful insects that infect the crop is the aphid and bush that spread at large rates in many fields, causing the spread of many pathogenic fungi. In addition to competing with plants for nutrients, With regard to fungi, there are many of them, such as fungi that cause smut and rust diseases of the crop, root and spike diseases, so this study came to clarify the most important agricultural pests and diseases facing the wheat crop, horticultural crops, and the most important ways and strategies for their development and agricultural development for the crop in Basra Governorate.